2011
DOI: 10.1080/1536710x.2011.571529
|View full text |Cite
|
Sign up to set email alerts
|

The Need to Know Caregiver Perspectives Toward Using Smart Home Technology

Abstract: This article reviews the literature on adults with serious mental illness, their caregivers, and smart home technology. The article provides compelling evidence for social workers to undertake research aimed at investigating caregivers' perceptions toward using smart home technology for care of adult family members or friends with a serious mental illness. Empirical support for using smart home technologies with adults with serious mental illness is provided, and recommendations for future social work research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…This decision support functionality is centred on monitoring through wearable, implantable and sensing devices to facilitate preventative care and detect adverse health incidents [17]. Other health researchers examine specific vulnerabilities, such as individuals living with serious mental illness, emphasising that caregivers rather than individuals are often the direct beneficiaries [34].…”
Section: The Functional Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision support functionality is centred on monitoring through wearable, implantable and sensing devices to facilitate preventative care and detect adverse health incidents [17]. Other health researchers examine specific vulnerabilities, such as individuals living with serious mental illness, emphasising that caregivers rather than individuals are often the direct beneficiaries [34].…”
Section: The Functional Viewmentioning
confidence: 99%
“…Chan et al [17], for example, highlight the potential for smart homes to incorporate wearable and implantable devices that can monitor various physiological parameters of patients. Giger et al [34] focus on those with serious mental illness. Orpwood et al [56] highlight the specific user-interface requirements of dementia sufferers.…”
Section: Prospective Users Of Smart Homesmentioning
confidence: 99%
“…These technological changes are the main source of impacts on lifestyle, social interactions, communications and the use of environments. Therefore, it is the crucial task of designers, architects and engineers to adapt the technological changes as the intelligent developments into the design of living environments [33][34][35]. Similar to the 1980s, when the arrival of personal computers, there was a growing interest towards researching on the circumstances of utilization of personal computers at home and the respective impacts on the lifestyle and behavior of users.…”
Section: Discussionmentioning
confidence: 99%
“…A review of current research showed that a number of overseas studies (Demiris et al, 2004;Coughlin et al, 2007;Mahmood et al, 2008;Mihailidis et al, 2008;Rialle et al, 2008;Sponselee et al, 2008;Wild et al, 2008;Giger and Markward, 2011;van Hoof et al, 2011;Mckenna et al, 2015;Peek et al, 2015) have explored the perceptions of elderly people and their caregivers of various types of SHT. SHT can be categorised into various functions, including enhancing personal safety; enhancing health monitoring; improving social interactions; and supporting living environment control.…”
Section: Connections Between Factors Influencing Adoption Of Smart-home Technologymentioning
confidence: 99%